Fundamentals of digital image processing : b a practical approach with examples in Matlab - Solomon, C. and Breckon, T (Wiley-Blackwell, 2011)
"Fundamentals of Digital Image Processing is an introductory text on the science of image processing and employs the Matlab programming language to illustrate some of the elementary, key concepts in modern image processing and pattern recognition drawing on specific examples from within science, medicine and electronics"--